THE SYNTHESIS OF SUFISM AND SOCIAL-EMOTIONAL LEARNING (SEL): STRENGTHENING STUDENT LEADERSHIP RESILIENCE IN MARGINALIZED MADRASAHS - Nur Khoiri; Mashudi Mashudi; Nasikhin Nasikhin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the management of holistic Islamic education in the context of structural poverty by integrating Sufism, mindfulness, and Social Emotional Learning (SEL) to strengthen students’ mental leadership resilience. The research uses a qualitative approach with a case study design and data analysis based on the Miles and Huberman model. The findings reveal that economic inequality has a multidimensional impact, hindering not only economic and social access but also affecting the mental health and educational quality of madrasah students. Despite living in fertile, resource-rich areas, many farmers still live in structural poverty, affecting their younger generations. Madrasah responds to this situation by developing mental resilience-based learning that integrates the values of Sufism, mindfulness, positive psychology, and SEL. However, these efforts are limited by the lack of professionals, inadequate infrastructure, and negative stigma from the community towards mental health issues. The implications of this study provide a basis for developing more holistic and context-specific educational policies and psychosocial interventions, particularly in disadvantaged areas. Additionally, this study offers key recommendations for collaboration among the government, educational institutions, and the community to build support systems that enhance students’ emotional and mental resilience, breaking the cycle of poverty and inequality sustainably.